2021
DOI: 10.1183/23120541.00178-2021
|View full text |Cite
|
Sign up to set email alerts
|

Association between lung function and future risks of diabetes, asthma, myocardial infarction, hypertension and all-cause mortality

Abstract: BackgroundWhile forced expiratory volume in 1 s (FEV1) is a hallmark of disease progression in chronic obstructive lung diseases, little is known about the relationship between baseline FEV1 and future risks of other medical conditions.ObjectiveTo study the association between baseline FEV1 and future risks of diabetes, asthma, myocardial infarction, hypertension and all-cause mortality.MethodsWe used data from the National Health and Nutrition Examination Survey and its Epidemiological Follow-Up Study. Our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The direction of association and mechanisms had remained unclear in the past [36], however there is now emerging evidence for a bi-directional causal association between lung function and diabetes [35]. An association between low vital capacity as a predictor of diabetes has been consistently found in previous observational studies [5,[37][38][39]. The possible explanations for this link have included reduced physical activity due to poor lung function leading to central obesity, hypoxaemia induced insulin resistance, adverse foetal or early-life conditions that effect organogenesis and metabolic pathway programming leading to insulin resistance and inflammation [37].…”
Section: Discussionmentioning
confidence: 97%
“…The direction of association and mechanisms had remained unclear in the past [36], however there is now emerging evidence for a bi-directional causal association between lung function and diabetes [35]. An association between low vital capacity as a predictor of diabetes has been consistently found in previous observational studies [5,[37][38][39]. The possible explanations for this link have included reduced physical activity due to poor lung function leading to central obesity, hypoxaemia induced insulin resistance, adverse foetal or early-life conditions that effect organogenesis and metabolic pathway programming leading to insulin resistance and inflammation [37].…”
Section: Discussionmentioning
confidence: 97%
“…Several longitudinal studies have shown an association between reduced lung volume or abnormal spirometry patterns and increased morbidity and mortality. Reduced FEV1 has been associated with an increased risk of occurrence of respiratory disease (Agusti et al, 2017;Shah et al, 2021) and metabolic abnormalities, including diabetes (Agusti et al, 2017;Shah et al, 2021), heart failure (Ramalho et al, 2022) and cardiovascular events (Agusti et al, 2017;Cuttica et al, 2018), and an increased risk of cardiovascular (Sin et al, 2005) and all-cause mortality (Agusti et al, 2017;Sarycheva et al, 2022). COPD or a reduced FEV1/FVC ratio has been associated with an increased risk of lung cancer (Kaaks (Collaro et al, 2021;Guo et al, 2021;Kaaks et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Among natural causes, chronic obstructive pulmonary disease (COPD) is one of the highest causes of excess mortality in people with schizophrenia or bipolar disorder, even higher than that of cardiovascular diseases (Saha et al, 2007;Hayes et al, 2015;Olfson et al, 2015;Correll et al, 2022). In the general population, both COPD and spirometrically determined impaired lung function are associated with increased morbidity and mortality (Sin et al, 2005;Guerra et al, 2010;Agusti et al, 2017;Honda et al, 2017;Cuttica et al, 2018;Collaro et al, 2021;Guo et al, 2021;Shah et al, 2021;Kaaks et al, 2022;Ramalho et al, 2022;Sarycheva et al, 2022;Dharmage et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia appears to be intricately linked to impaired lung function, as having a lower forced expiratory volume in 1 s (FEV1) is associated with an increased likelihood of developing DM in the future (126). Moreover, fasting plasma glucose and HbA1c levels exhibit an inverse relationship with lung function test results, indicating the potential impact of glycemic control on respiratory health (127,128).…”
Section: Asthma and Dmmentioning
confidence: 99%